Pengaruh CR, DAR Dan DER Terhadap NPM Pada PT Perusahaan Gas Negara Tbk Periode 2013-2022 - Aprilia; Ernia Missa, Eka; Susilo Jahja, Adi (Shofanah Media Berkah, 2023)
The purpose of this study is to determine the effect of current ratio (CR), debt to asset ratio (DAR) and debt to equity ratio (DER) on net profit margin (NPM) of PT Perusahaan Gas Negara Tbk. In terms of net profit margin (NPM), current ratio (CR), debt to asset ratio (DAR), and debt to equity ratio (DER), the company's financial performance is evaluated analytically for several years,The financial statements of PT Perusahaan Gas Negara are the source of research data. One type of research conducted is quantitative research. The results showed that the current ratio (CR), debt to equity ratio (DER), and debt to asset ratio (DAR) partially did not have a significant effect on net profit margin (NPM). Simultaneously, the current ratio (CR), debt to equity ratio (DER), and debt to asset ratio (DAR) have a significant effect on net profit margin (NPM). In summary, in several time periods PT Perusahaan Gas Negara showed growth in the current ratio, debt to asset ratio, and debt to equity ratio. Company management can leverage the findings of the analysis to guide better financial resource management decisions that will improve the company's financial performance in the future.